Dynamic behavior of rearranging carbocations – implications for terpene biosynthesis - Hare, Stephanie R.; Tantillo, Dean J. (Beilstein Journal of Organic Chemistry, 2016)
This review describes unexpected dynamical behaviors of rearranging carbocations and the modern computational methods used to elucidate these aspects of reaction mechanisms. Unique potential energy surface topologies associated with these rearrangements have been discovered in recent years that are not only of fundamental interest, but also provide insight into the way Nature manipulates chemical space to accomplish specific chemical transformations. Cautions for analyzing both experimental and theoretical data on carbocation rearrangements are included throughout.
Keywords: carbocation; density functional theory; dynamics; mechanism; terpene